2014
DOI: 10.1161/strokeaha.114.006116
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Lesions Are Associated With Hospital Admissions Because of Hip-Fractures and Trauma After Ischemic Stroke

Abstract: The Helsinki Stroke Aging Memory (SAM) cohort consists of 1622 consecutive patients with suspected stroke (all Finnish, white) admitted to the Helsinki University Central Hospital between December 1, 1993 and March 30, 1995. Patients without ischemic stroke (n=175), intracerebral (n=229), or subarachnoid (n=69) hemorrhage were Background and Purpose-Cerebral white matter lesions (WMLs), a surrogate for cerebral small-vessel disease, have been shown to be associated with decreasing mobility, gait instability,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…While the already reported association of stroke and L-A reportedly impairs DLA and cognition [34-38], curiously very few information exists regarding manifestations of L-A and its possible association with ASD, except only in the case of anemia [39]. Results presented here support the hypothesis that general organic ailments influence the development of L-A, reaching an impairment degree similar to that observed in stroke.…”
Section: Discussionsupporting
confidence: 80%
“…While the already reported association of stroke and L-A reportedly impairs DLA and cognition [34-38], curiously very few information exists regarding manifestations of L-A and its possible association with ASD, except only in the case of anemia [39]. Results presented here support the hypothesis that general organic ailments influence the development of L-A, reaching an impairment degree similar to that observed in stroke.…”
Section: Discussionsupporting
confidence: 80%
“…The white matter lesions burden positively correlates with age, with a higher prevalence of severe SVD in patients older than 76 years (8). A significant involvement of the brain by SVD is linked with the development of geriatric syndromes (1, 2) and can truly represent a clinical entity able to cause dizziness and falls in the elderly (6, 9). Eye movement control pathways for saccades and pursuit involve ascending and descending fibers between frontal and parietal cortex, basal ganglia, brainstem, and cerebellum (13).…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been established how SVD contributes to the development of cognitive decline and dementia (3, 4) and falls (5, 6), little is known about SVD as a possible cause of dizziness. White matter hyperintensities on T2-weighted and fluid-attenuated inversion recovery sequences on magnetic resonance imaging (MRI) are the radiological expression of SVD and represent a well-known marker of a higher risk of cerebral, cerebellar, and brainstem stroke (7).…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that WMLs are associated with hospital admissions because of hip fractures, trauma, and recurrent stroke (11, 12).…”
Section: Introductionmentioning
confidence: 99%
“…Severe white matter lesions (WMLs), one imaging expression of cerebral small vessel disease, are associated with an increased risk of functional decline, morbidity, and death in independent outpatients and also in acute stroke patients (5)(6)(7). The international Leukoaraiosis and Disability in the Elderly (LADIS) study has shown that severe WMLs more than double the risk of transition from an autonomous to dependent status in a three-year follow-up (8).…”
Section: Introductionmentioning
confidence: 99%